A De Novo Novel Cardiac Ryanodine Mutation (Ser4155Tyr) Associated with Catecholaminergic Polymorphic Ventricular Tachycardia. Issue 6 (23rd October 2013) - Mantziari, Lilian; Vassilikos, Vassilios; Anastasakis, Aris; Kotsaka, Xanthippi; Paraskevaidis, Stelios; Styliadis, Ioannis H; Luria, David
<x xml:space="preserve">Abstract</x> We describe the case of a 14‐year‐old girl with a history of syncopal episodes triggered by stress or exercise. Catecholaminergic polymorphic ventricular tachycardia was diagnosed with the aid of an implantable loop recorder. The genetic testing of the patient and her family revealed a de novo novel missense mutation (Ser4155Tyr) in the exon 90 of the ryanodine receptor gene. This mutation affects a highly conserved residue (S4155) and results to replacement of serine (S) with tyrosine (Y) leading to change in physical and chemical properties. The girl was treated with an implantable defibrillator, metoprolol and flecainide. Over 1 year of follow‐up she had no recurrence of ventricular tachycardia.